Brain Penetrable Histone Deacetylase 6 Inhibitor SW-100 Ameliorates Memory and Learning Impairments in a Mouse Model of Fragile X Syndrome - Kozikowski, Alan P; Shen, Sida; Pardo, Marta; Tavares, Maurício T; Szarics, Dora; Benoy, Veronick; Zimprich, Chad A; Kutil, Zsófia; Zhang, Guiping; Bařinka, Cyril; Robers, Matthew B; Van Den Bosch, Ludo; et al. (ACS chemical neuroscience, 2019)
Disease-modifying therapies are needed for Fragile X Syndrome (FXS), as at present there are no effective treatments or cures. Herein, we report on a tetrahydroquinoline-based selective histone deacetylase 6 (HDAC6) inhibitor SW-100, its pharmacological and ADMET properties, and its ability to improve upon memory performance in a mouse model of FXS, Fmr1-/- mice. This small molecule demonstrates good brain penetrance, low-nanomolar potency for the inhibition of HDAC6 (IC50 = 2.3 nM), with at least a thousand-fold selectivity over all other class I, II, and IV HDAC isoforms. Moreover, through its inhibition of the α-tubulin deacetylase domain of HDAC6 (CD2), in cells SW-100 upregulates α-tubulin acetylation with no effect on histone acetylation and selectively restores the impaired acetylated α-tubulin levels in the hippocampus of Fmr1-/- mice. Lastly, SW-100 ameliorates several memory and learning impairments in Fmr1-/- mice, thus modeling the intellectual deficiencies associated with FXS, and hence providing a strong rationale for pursuing HDAC6-based therapies for the treatment of this rare disease.
Keywords: Fragile X Syndrome; Histone Deacetylase 6; Quinolines; syndrom fragilního X; Benzamides; Cognition; Memory; hipokampus; acetylated α-tubulin; Disease Models, Animal; posttranslační úpravy proteinů; memory and learning impairments; Mice; učení; benzamidy; permeability; Ames negative; paměť; kognice; modely nemocí na zvířatech; Protein Processing, Post-Translational; zvířata; histondeacetylasa 6; inhibitory histondeacetylas; Phenylhydroxamate; Histone Deacetylase Inhibitors; Learning; myši; chinoliny; Hippocampus; Animals